Growth and influence of a porous iron oxide nanolayer on LiMn2O4 in an aqueous rechargeable lithium‐ion battery. Issue 4 (4th March 2020) - Schuppert, Nicholas D.; Mukherjee, Santanu; Bates, Alex; Jasinski, Jacek B.; Lee, Sang C.; Park, Sam
Abstract: A porous iron oxide nanolayer coating is grown on LiMn2 O4 by a facile in‐situ method. Evolution of this coating and its influence on the structural retention and electrochemical activity of LiMn2 O4 is examined and compared to a control in the environment of an aqueous rechargeable lithium‐ion battery. Two coinciding mechanisms of porous iron oxide nanolayer deposition and their depency on electrolyte pH are identified and discussed. The coating is found to significantly reduce Li2 MnO3 surface formation, a major source of capacity fade in LiMn2 O4 electrodes, thereby improving the structural retention. The nanolayer was also found to improve the electrochemical stability of the underlying LiMn2 O4 in the potential window of lithium intercalation, reduce the growth rate of mass transfer and solid electrolyte interface resistances over the control, while also providing reduced charge transfer resistances over the pristine LiMn2 O4 material. The totality of these improvements provided by the porous iron oxide nanolayer preserved the electrochemical and structural integrity of LiMn2 O4 over the course of 500 deep discharge cycles in aqueous media.